2019
DOI: 10.1186/s12967-019-1770-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of interleukin (IL)-1 beta inhibition on the epithelial-to-mesenchymal transition (EMT) of renal tubular and hepatic stellate cells

Abstract: BackgroundThe epithelial to mesenchymal transition (EMT) is a multi-factorial biological mechanism involved in renal and hepatic fibrosis and the IL-1 beta has been assumed as a mediator of this process although data are not exhaustive. Therefore, the aim of our study was to evaluate the role of this cytokine in the EMT of renal proximal tubular epithelial cells (HK-2) and stellate cells (LX-2) and the protective/anti-fibrotic effect of its inhibition by Canakinumab (a specific human monoclonal antibody target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 50 publications
(50 reference statements)
1
43
0
Order By: Relevance
“…Particularly noteworthy, the Canakinumab Anti-inflammatory Thrombosis Outcomes Study (CANTOS) revealed that IL-1β inhibition with the neutralizing antibody canakinumab decreases both the incidence and mortality of lung cancer in patients with atherosclerosis co-morbidities 13 . Although our previous studies and those from others demonstrated that acute IL-1β exposure induces the expression of genes associated with transformation, invasion, and metastasis in multiple malignancies, including lung cancer, the impact of chronic IL-1β exposure, which may be more physiologically relevant, has not yet been defined [14][15][16][17][18][19][20] .…”
mentioning
confidence: 86%
“…Particularly noteworthy, the Canakinumab Anti-inflammatory Thrombosis Outcomes Study (CANTOS) revealed that IL-1β inhibition with the neutralizing antibody canakinumab decreases both the incidence and mortality of lung cancer in patients with atherosclerosis co-morbidities 13 . Although our previous studies and those from others demonstrated that acute IL-1β exposure induces the expression of genes associated with transformation, invasion, and metastasis in multiple malignancies, including lung cancer, the impact of chronic IL-1β exposure, which may be more physiologically relevant, has not yet been defined [14][15][16][17][18][19][20] .…”
mentioning
confidence: 86%
“…For instance, KCs can respond to exposure to LPS by binding to TLR4 which leads to production of inflammatory cytokines (TNF-α, IL-1β, IL-6, IL-12, IL-18, etc.) and other chemokines [72], most of them being actively involved in HSCs activation (Table 2) [5,[73][74][75]. Other macrophages recruited to the liver in the case of inflammation, are also involved in secretion of pro-and anti-inflammatory cytokines, depending on their type (proinflammatory M1 or immunosuppressive M2, respectively).…”
Section: Inflammatory Signals From Kupffer Cells and Other Inflammatimentioning
confidence: 99%
“…Western blot using specific monoclonal antibodies of α-SMA and fibronectin confirmed our previous observation and showed the elevation in the steady-state levels of both cell-associated ECM proteins ( Figure 2C ). Because HG upregulates fibronectin ( 27 ), and IL-1 treatment causes a fibrotic-like state in human HK-2 cells in vitro ( 28 ), we tested the possibility that the IL-1α-dependent primary intrinsic inflammation, which stimulates cells to adopt an activated state characterized by enhanced expression of ECM protein production, can be attenuated by IL-1Ra. In support of our hypothesis, when tested in an animal rat model, administration of an IL-1Ra almost completely abrogated tubular atrophy ( 29 ).…”
Section: Resultsmentioning
confidence: 99%